PROBLEM MIGRASI SIARAN TV ANALOG KE DIGITAL - Redi Panuju (Hikmah, 2019)
This article reveals the problem of TV broadcast migration from analog systems to digital systems. The method used in this study is textual construction by analyzing reliable text sources from reports, journals, regulations, and others. The existing text is analyzed based on the Functional Structural approach of Talcott Parson. The results of this study indicate that Indonesia's delay in migrating to a digital system cannot be separated from the interests of old players who tend to be safe in their current position. Old players tend to extend the status quo to continue to enjoy the capital effects of the channel monopoly provided by the old law (Law No.32 of 2002). Moreover, these old players tend to have a strong political role, because the owners are status as administrators of Political Parties or even the chairman of Political Parties. Thus the influence of dictating the legislature in Senayan is also very strong.Keywords: Analog Systems, Digital Systems, Broadcast Migration, Status Quo, Party Chair.Artikel ini mengungkapkan problem migrasi siaran TV dari sistem analog ke sistem digital. Melalui sistem ini satu saluran dapat digunakan untuk bersiaran 5 sampai 6 stasiun Televisi. Metode yang digunakan dalam kajian ini adalah kontruksi tekstual dengan menganalisis sumber- sumber teks terpercaya dari pemberitaan, jurnal, regulasi, dan lainnya. Teks yang ada dianalisis berdasarkan pendekatan Struktural Fungsional dari Talcott Parson. Hasil kajian ini menunjukkan keterlambatan Indonesia bermigrasi ke system digital tak lepas dari kepentingan pemain lama yang cenderung sudah aman dalam posisinya sekarang. Pemain lama cenderung memperpanjang status quo untuk tetap menikmati efek capital dari monopoli saluran yang diberikan oleh undang undang lama (UU No.32 tahun 2002). Apalagi para pemain lama ini cenderung memiliki peran politik yang kuat, disebabkan para pemiliknya berstatus sebagai pengurus Partai Politik atau bahkan ketua Parpol. Dengan demikian pengaruhnya mendikte legislatif di Senayan juga sangat kuat.Kata Kunci: Sistem Analog, Sistem Digital, Migrasi Penyiaran, Status Quo, Ketua Partai.